Hypoxia-inducible factor-2α promotes fibrosis in non-alcoholic fatty liver disease by enhancing glutamine catabolism and inhibiting yes-associated protein phosphorylation in hepatic stellate cells - Yan, Ranran; Cai, Hao; Zhou, Xiaofeng; Bao, Guodan; Bai, Zhenzhong; Ge, Ri-li (Frontiers in Endocrinology, 2024)
Non-alcoholic fatty liver disease (NAFLD) has a high global prevalence and affects approximately one-third of adults, owing to high-fat dietary habits and a sedentary lifestyle. The role of hypoxia-inducible factor 2α (HIF-2α) in NAFLD progression remains unknown. This study aimed to investigate the effects of chronic hypoxia on NAFLD progression by examining the role of hypoxia-inducible factor 2α (HIF-2α) activation and that of hepatic stellate cell (HSC)-derived myofibroblasts through glutaminolysis. We hypothesised that hypoxia exacerbates NAFLD by promoting HIF-2α upregulation and inhibiting phosphorylated yes-associated protein (YAP), and that increasing YAP expression enhances HSC-derived myofibroblasts. We studied patients with NAFLD living at high altitudes, as well as animal models and cultured cells. The results revealed significant increases in HSC-derived myofibroblasts and collagen accumulation caused by HIF-2α and YAP upregulation, both in patients and in a mouse model for hypoxia and NAFLD. HIF-2α and HIF-2α-dependent YAP downregulation reduced HSC activation and myofibroblast levels in persistent chronic hypoxia. Furthermore, hypoxia-induced HIF-2α upregulation promoted YAP and inhibited YAP phosphorylation, leading to glutaminase 1 (GLS1), SLC38A1, α-SMA, and Collagen-1 overexpression. Additionally, hypoxia restored mitochondrial adenosine triphosphate production and reactive oxygen species (ROS) overproduction. Thus, chronic hypoxia-induced HIF-2α activation enhances fibrosis and NAFLD progression by restoring mitochondrial ROS production and glutaminase-1-induced glutaminolysis, which is mediated through the inhibition of YAP phosphorylation and increased YAP nuclear translocation. In summary, HIF-2α plays a pivotal role in NAFLD progression during chronic hypoxia.